Somatic Treatments Excluding Psychopharmacology in Obsessive-Compulsive Disorder: A Review - Atmaca, Murad (Bentham Science Publ Ltd, 2013)
Somatic treatments other than psychotropic drugs are increasingly used in the patients with obsessive compulsive disorder (OCD), however there has been little systematic review of them. Therefore, the present review deals with a variety of somatic treatment methods excluding psychotropic drugs. A literature search was performed on the PubMed database from the beginning of 1980, to September 2012, for published English, Turkish and French- language articles of somatic treatment approaches (excluding psychopharmacological agents) in the treatment of OCD. The search was carried out by using some terms in detail. Afterwards, the obtained investigations on electroconvusive therapy (ECT), deep brain stimulation (DBS), neurosurgical methods and transcranial magnetic stimulation (TMS) were presented. Although psychopharmacological treatment and psychotherapeutic approaches are primary treatment modalities in the management of OCD, other somatic treatment options seem to be used as alternatives, especially for patients with treatmentresistant OCD.
Keywords: Somatic treatment; review; obsessive compulsive disorder